Sayaw Mindanao designing an interactive CD-ROM for an instructional dance material - Bengan, Catherine Rose B.
Dugso Sungco, an indigenous dance from the Talaandig tribe in Bukidnon, was preserved in a medium in a form of an instructional material. Due to apparent limitations of video as a medium of instruction, the material was subjected to the non-linear environment of interactive multimedia. This thesis production focused on interface design and the navigational structure of the aforementioned material. At the end of the process, I was able to create a design faithful to the tribe's own aesthetic by utilizing authentic patterns and colors of their garments. In preserving an indigenous knowledge to avoid discrepancies.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts